The Effect Of Discovery Learning And Science Basic Skill Knowledge On The Results Of Student Learning MA Roudhotul Ulum Seputih Mataram Class Ix - Rias Choirinnisa (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2020)
Biological learning experienced by students directly will be easier to help students understand the material. The teacher must design the learning process of biology, so that students have a high curiosity so as to increase students' knowledge of the material in accordance with the implementation of the government, where students are more active in learning activities in the classroom. The learning process plan can be stated in the Student Worksheet (LKS) which will be developed in accordance with the state of the school environment and the development of the existing curriculum. LKS with discovery learning method referred to in this study is LKS that is oriented to the emergence of problems that are engineered by teachers related to real life. This problem, will be solved by students through a direct discovery by students. Shiva Worksheet (LKS) with discovery learning method is expected to make students 'learning interest higher and students motivated to learn, so as to improve student learning outcomes, in addition it can improve students' psychomotor / skills by holding a simple practicum to prove the theory existing theories, so students will be easy to understand and find answers to existing problems.